2020
DOI: 10.1007/s11104-020-04745-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations among the communities of soil-borne pathogens, soil edaphic properties and disease incidence in the field pea root rot complex

Abstract: Background and aims Field pea production is greatly impacted by multiple soil-borne fungal and oomycete pathogens in a complex. The objectives of this research were to 1) identify the soil-borne pathogens associated with field pea in North Dakota and; 2) develop prediction models incorporating the occurrence of the soil-borne pathogen communities, soil edaphic properties and disease incidence. Methods Soil and plants were sampled from 60 field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…F. sporotrichioides (S) is a common, ineffectual agricultural and grassland pathogen [98], commonly isolated from corn and other cereal crops [99]. F. sporotrichioides (S) RAs have been reported to be negatively associated with soil pH [100], as is the case in this study showing greater RAs from the CCC rotation, which has significantly lower pH compared to the other rotations [25]. Behnke, Zabaloy, Riggins, Rodriguez-Zas, Huang and Villamil [25] also found that fungal ITS gene copy numbers were increased in the CCC rotation compared to SSS.…”
Section: Discussionmentioning
confidence: 99%
“…F. sporotrichioides (S) is a common, ineffectual agricultural and grassland pathogen [98], commonly isolated from corn and other cereal crops [99]. F. sporotrichioides (S) RAs have been reported to be negatively associated with soil pH [100], as is the case in this study showing greater RAs from the CCC rotation, which has significantly lower pH compared to the other rotations [25]. Behnke, Zabaloy, Riggins, Rodriguez-Zas, Huang and Villamil [25] also found that fungal ITS gene copy numbers were increased in the CCC rotation compared to SSS.…”
Section: Discussionmentioning
confidence: 99%
“…Five single-spore isolates (SSI), S4C ( F. solani ), F4A ( F. avenaceum ), F037 ( F. acuminatum ), F039 ( F. proliferatum ), and FG2 ( F. graminearum ), representing the Fusarium species most frequently recovered from symptomatic pea plants in root rot surveys in Alberta, were used to screen the parental cultivars “00-2067” and “Reward.” Briefly, to obtain the SSIs, surface-sterilized pieces of root tissue with disease lesions were placed on potato dextrose agar (PDA) and incubated at 25°C for 2–3 days and then transferred to the peptone-pentachloronitrobenzene (PCNB) medium for further selection. Mycelial tips of the fungal isolates were cut from selected colonies under a stereomicroscope (Zeiss Axio Scope A1, Carl Zeiss Canada Ltd., Canada), and the water agar (WA) procedure was used to obtain SSI ( Zitnick-Anderson et al, 2020 ). The species designation of each of the SSIs was confirmed based on morphology and evaluation with the PCR primer sets ITS4/ITS5 and EF-1/EF-2, while isolate virulence was confirmed by fulfilling Koch’s postulates ( Feng et al, 2010 ; Chen et al, 2014 ; Zhou et al, 2014 ; Wu et al, 2017 ; Chang et al, 2018 ; Zitnick-Anderson et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, monogenic resistance is easy to select and has been achieved in some soilborne diseases of legumes, but the rapid evolution of pathogens can easily break down the existing levels of resistance. So, the understanding and evaluation of soilborne diseases by efficient identification and screening techniques is a requirement for the implementation of effective control strategies and resistance breeding [ 49 , 52 ]. Therefore, in this review, some of the important pea rhizospheric diseases are deliberated.…”
Section: Pea Rhizospheric Diseasesmentioning
confidence: 99%
“…The identification of resistance sources within germplasms and a combination of practical phenotypic evaluation standards and host resistance genotyping can improve sustainable Fo p control strategies in the long term [ 57 , 75 , 76 ]. So, the knowledge of the fungal patho-systems, genetics and physiological variations can inform sustainable resistance breeding strategies [ 52 , 64 ]. Qualitative resistance for Fop race 1, 5 and 6 have been identified and deployed into pea varieties using classical breeding [ 62 , 77 ].…”
Section: Pea Rhizospheric Diseasesmentioning
confidence: 99%
See 1 more Smart Citation